The Road Less Traveled A New Psychology of Love, Traditional Values and Spiritual Growth - M. Scott Peck (New York Simon and Schuster, 1978)
Discusses the nature of loving relationships in the context of traditional psychological and spiritual insights.
Keywords: Maturation ( Psychology); Psychiatry and Religion Self-actualization (Psychology) Maturation (Psychology) Interpersonal relations. Love. Values. Spirituality. Maturation (Psychology.) Interpersonal Relations. Religion and Psychology. Self-Assessment. Social Values. Actualisation de soi. Maturation (Psychologie) Relations humaines. Amour -- Aspect psychologique. Valeurs (Philosophie) Spiritualité Psychiatry and religion. Psychoanalysis and religion